Identifikasi Prilaku Konsumen dalam Pengambilan Keputusan Penggunaan Jasa Pengiriman Barang - Afrizal; Rangga Wisanggara; Alfi Syukri Rama; Riandy Mardhika Adif (SAFE-Network, 2022)
The package delivery service business experiences intense competition between transportation companies. This form of competition is marked by the proliferation of shipping service companies in Indonesia. Many of these companies are managed by the private sector and only one is managed by the state, namely PT. Pos Indonesia (Persero). PT. Pos Indonesia (Persero) has one package delivery service company, namely PT. Indonesian Postal Delivery Services (Persero). This company is a state company that provides public services, but competes strictly with private companies. Currently, many people do not use the services provided by PT. Pos Indonesia (Persero), so that it is forgotten by the public. Factors that greatly influence are the many delivery service industries that offer added value. The most widely offered offer is speed and accuracy to the destination, wider coverage and low cost. This study aims to identify the factors that influence the satisfaction of consumers who are loyal to using the services of PT. Indonesian Postal Delivery Services (Persero). The method used is descriptive quantitative research on consumer decision factors at the Air Bangis post office in West Pasaman, West Sumatra. The results obtained are that customer trust has no positive and insignificant effect on consumer decisions with a significant level of 0.451. Brand Recall has a positive and significant effect on Consumer Decisions with a significance level of 0.001. Word of Mouth has a positive and significant effect on consumer decisions with a significance level of 0.000. So that this research can be used as a recommendation by package service providers in identifying factors in retaining customers.